Poems of the Elder Edda - Terry, Patricia, 1929-; Dunn, Charles W. (Middle Ages series., 1990)
A revised edition of Terry's classic Poems of the Vikings, long out of print. This edition has a new preface, updated references, and expanded notes and glossary. The translation itself has been extensively revised.